Performance Measurement Of Small Breeding Business In North Bengkulu Regency: Application Of Balanced Scorecard (Bsc) Method - Muly Apriansyah; Ketut Sukiyono; Mohammad Chozin (Journal of Agri Socio Economics and Business, 2019)
The purpose of this research first is to evaluate the performance of Usaha Perbenihan Kecil (Small Breeding Businesses =UPK) from the perspective of financial, customers, internal business process, as well as learning and growth. The second objective is to identify the factors that performance in supporting the success of UPK solutions and fix the problem. Two UPKs are cencused and interviewed, namely, UPK Karya Mandiri and UPK Karya Tani. Balanced Scorecards (BSC) is applied to measure financial and non-financial performances. The results show that performances of two UPKS are categorized a good performance in all perspectives, with exception to MCE index. This indicates that both UPKs should continouesly improve their internal business.